Analysis of the Influence of Risk Management Functions, Corporate Governance and External Pressures on the Quality of the Company's Financial Statements - Sudirja, Sudirja; Martias, Andi; Rachmawati, Susan; Wahyuhening F, Firstianty (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
The accuracy and transparency of financial statements are critical indicators of a company's credibility and sustainability. In an increasingly dynamic business environment, companies face growing internal and external challenges that demand stronger financial accountability. This study aims to examine the impact of risk management functions, good corporate governance, and external pressures on the quality of financial statements. The independent variables in this study include the effectiveness of risk management, the implementation of corporate governance principles, and external stakeholder pressures, while the dependent variable is the quality of the company's financial statements. The research adopts a verification method using quantitative analysis, based on primary data collected through questionnaires measured using the Likert scale. The sample consists of 197 randomly selected company employees. Data were analyzed using descriptive statistics, data quality tests, classical assumption testing, and hypothesis testing, with SPSS software. The findings indicate that the risk management function, good corporate governance, and external pressures all have a significant positive impact on the quality of financial statements. These results imply that improving internal control systems, governance structures, and responsiveness to external demands contributes meaningfully to financial transparency and reliability, enhancing investor confidence and long-term corporate performance.